Woolly hair nevus type 2 : A case report - Nitinawarat, Jantakan; Panchaprateep, Ratchathorn; Rerknimitr, Pawinee (Thai Journal of Dermatology, 2015)
Woolly hair nevus is a rare, nonhereditary disorder of the hair shaft. Approximately 50% of the patients with woolly hair nevus are associated with epidermal nevus (woolly hair nevus type 2). Other cutaneous and extracutaneous lesions have been reported in association with this condition. In this report, we describe a patient with woolly hair nevus type 2. A 52-year-old woman presented with fine, curly, woolly-textured hair on top of verrucous, hyperpigmented plaques. Scanning electron microscopic and histopathological findings are compatible with woolly hair nevus type 2. There is no other systemic manifestation found.